2014
DOI: 10.1089/jpm.2013.0533
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students as Hospice Volunteers: Reflections on an Early Experiential Training Program in End-of-Life Care Education

Abstract: Hospice volunteering during preclinical years may provide valuable experiential training for MS-1s in caring for seriously ill patients and their families by fostering personal reflection and empathic skills, thereby providing a foundation for future patient encounters during clinical training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 25 publications
1
26
0
3
Order By: Relevance
“…Research reports show that not only nursing and medical students, but also professionally active nurses and physicians do not consider themselves adequately prepared to provide care to dying patients. This is evidenced by opinions shared by physicians and nurses as well as by patients and their families [4,6,[8][9][10][11]. One must realise that the process of dying and death is special and, at the same time, difficult for the patients and their families on the one hand, but, on the other hand, for the medical staff as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research reports show that not only nursing and medical students, but also professionally active nurses and physicians do not consider themselves adequately prepared to provide care to dying patients. This is evidenced by opinions shared by physicians and nurses as well as by patients and their families [4,6,[8][9][10][11]. One must realise that the process of dying and death is special and, at the same time, difficult for the patients and their families on the one hand, but, on the other hand, for the medical staff as well.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of EOL requires from those working with dying persons not only appropriate knowledge and skills, but also deep empathy and a mature attitude towards his/her own and someone else's death. Regrettably, the results of research carried out globally and in Poland have shown that nursing and medical students do not feel prepared to provide care to patients at the end of their lives [5][6][7], and it is only after they start career that they acquire knowledge in this respect -this unfortunately acts against the quality of care [4].…”
mentioning
confidence: 99%
“…Medical students who performed some kind of voluntary work in a hospice reported that the work had intimately transformed them, 35 which suggests a process of self-reflection.…”
Section: Think There Is Great Mutual Learning On Both Sides! I Learmentioning
confidence: 99%
“…To be effective, they should be accompanied by both regular support from recruited volunteers and communication activities to make them better known by facilities that are potentially interested. Another direction mentioned simultaneously by American [66] and Canadian [67] authors consists in raising the awareness of future physicians about issues linked to the end of life by proposing they spend several hours as a volunteer in a hospice during their first year of study. This work shows that the students who followed these programs-pilot programs for now-acquired very positive experience for themselves and for their future profession, whether in reducing fear in the face of death, in encouraging their personal reflections, or in learning to better communicate with patients and families.…”
Section: Palliative Care Volunteers In Pcsts and In Traditional Care mentioning
confidence: 99%